Body growth description of male and female from three broilers strains in the hot climate - Do Nascimento, Dáphinne Cardoso Nagib; Dourado, Leilane Rocha Barros; De Siqueira, Jefferson Costa; Das Chagas Fontenele De Albuquerque, Francisca; Marques, Roberto Melo; Marcato, Simara Marcia; Sakomura, Nilva Kazue [UNESP]; Farias, Leonardo Atta (Universidade Estadual de Londrina, 2020)
To evaluate the growth of males and females from three broiler strains (Cobb 500, Ross 308, and Hubbard Flex) we used a completely randomized experimental design with a factorial arrangement (3 strains and 2 sexes) and six replicates of 60 birds each, 2160 chicks of both sexes in total followed for 56 days. Once a week, the birds from each pen were weighed to estimate the average weight. The sample birds were fasted for 24 hours, re-weighed, slaughtered, eviscerated, and dissected to obtain the breast, thigh and drumstick cuts. The fitted Gompertz equations were used for each strain, and sex, for the fasted weight, and the weight of breasts, thighs, and drumsticks. To verify the effect of strain on the Gompertz curve parameters we assessed the weight at maturity (Wm), rate of maturing (b), and the time at which maximum growth rate was attained (t∗) for both sexes and verified the equivalence of parameters and identity of non-linear models. For the fasted weight the rate of maturing was very similar for all strains and sexes, but the Hubbard strain showed the highest Wm and t∗. The Wm parameter was common for most cuts among the strains, and the Hubbard was the dominant strain with the highest b parameter. All three parameters were similar for the male breast weight, and only one equation required adjustment to describe the breast weight growth for the three strains. Individually adjusted equations were necessary to describe the weight of drumsticks because females showed no similarity in any of the parameters for any strain.
Keywords: Carcass yield; Genetic; Poultry industry